A Study of Serum Ferritin Level in Female Patient with Alopecia - Pradhan, Manish; Rai, Dipa; Paudel, Sagar (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Introduction: Total body iron store is an integral factor in the development of hair follicle. Numerous studies have been done seeking for the relationship between body iron store and various forms of chronic diffuse hair loss, with relatively contradictory findings in various reports in these studies. The main objective of this study is to find out if there is any association between total body iron store and various types of chronic diffuse hair loss in females in reproductive age. Materials and Methods: This is a hospital based case control study conducted in Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. Sixty female patients of age group 15-50 years with chronic diffuse hair loss with equal number of age- and sex- matched controls were studied. Both of the study groups were evaluated for various parameters of iron status. Results: The mean value of serum ferritin in cases was significantly lower as compared to controls (p=0.018). Patients with alopecia areata (p=0.008) and androgenetic alopecia (p=0.021) had significantly lower serum ferritin, whereas there was no statistically significant difference in telogen effluvium and controls (p=0.857).The mean value of hemoglobin, hematocrit and mean corpuscular hemoglobin was found to be significantly lower in alopecia areata and androgenetic alopecia. However, there was no statistically significant difference in RBC indices of patients of telogen effluvium and controls. Conclusion: Diffuse chronic hair loss shows definite association with serum ferritin and various RBC indices in female of reproductive age group. Alopecia areata and androgenetic alopecia show major association with total body iron stores. Keywords: alopecia areata; androgenetic alopecia; serum ferritin; telogen effluvium.